2020
DOI: 10.1007/s00213-020-05534-8
|View full text |Cite
|
Sign up to set email alerts
|

Does acute stress influence the Pavlovian-to-instrumental transfer effect? Implications for substance use disorders

Abstract: Rational The ability of conditioned stimuli to affect instrumental responding is a robust finding from animal as well as human research and is assumed as a key factor regarding the development and maintenance of addictive behaviour. Objectives While it is well known that stress is an important factor for relapse after treatment, little is known about the impact of stress on conditioned substance-associated stimuli and their influence on instrumental responding. Methods We administered in the present study a Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Noradrenaline (time: b=-0.06, t(298)=-2. 30 ----Figure 5 ----No significant group or order differences after the Cocaine-Cue-Video were found for AUC G (ps>.058; Tab. 2).…”
Section: Neuroendocrine Responsementioning
confidence: 93%
See 2 more Smart Citations
“…Noradrenaline (time: b=-0.06, t(298)=-2. 30 ----Figure 5 ----No significant group or order differences after the Cocaine-Cue-Video were found for AUC G (ps>.058; Tab. 2).…”
Section: Neuroendocrine Responsementioning
confidence: 93%
“…This is in line with Back et al 28 who did not observe enhanced cortisol or subjective stress reactivity to a cue after the TSST in prescription opioid users. Nor did the socially evaluated cold pressor stress test differentially influence the impact of a smoking-related cue on instrumental responding for a smoking-related reward in a Pavlovian-to-instrumental transfer paradigm, thus, was not potentiating drug-seeking behavior 30 .…”
Section: Interaction Between Psychosocial Stress and Cravingmentioning
confidence: 95%
See 1 more Smart Citation
“…At last, while habit was assumed to be the mechanism that the present IC training was directed towards, this assumption was not tested directly, for example by administering a Pavlovian to instrumental Transfer task which aims to assess the effect of conditioned stimuli on instrumental responding (e.g., Steins-Loeber et al, 2020 ).…”
Section: Limitationsmentioning
confidence: 99%
“…Much of the work on stress and reward (such as the work on cue-induced reinstatement) cannot distinguish between Pavlovian and instrumental processes. In humans, high anxiety levels (not experimentally induced) have been associated with deficits in SO-PIT (Quail, Morris et al 2017), whereas experimentally induced stress just prior to testing has been shown to promote SO-PIT (Pool, Brosch et al 2015) and to not alter SS-PIT (Steins-Loeber, Lörsch et al 2020). In rodents, acute stress just prior to testing has been shown not to affect SO-PIT expression (Pielock, Braun et al 2013), but to transiently block SS-PIT expression (Morgado, Silva et al 2012).…”
Section: Introductionmentioning
confidence: 99%